2018
DOI: 10.1177/0021886318757997
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the Behavioral Properties of Commitment and Resistance to Organizational Change

Abstract: The goal of this study was to develop and validate behavioral measures of employees' commitment and resistance toward organizational change. The scales were developed using an "imposed etic-emic-derived etic" perspective, the act frequency approach, principal components and confirmatory factor analysis. Five Canadian government departments participated across the three stages of the study. The measures were tested in four departments (N = 583). Both scales were found to be valid and reliable. This study suppor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 82 publications
(124 reference statements)
1
28
0
1
Order By: Relevance
“…Individuals with commitment to change would feel attached and strive to make the change a success (Herscovitch & Meyer, 2002). Previous research proved that com-mitment to change could increase behavioural support for change and creative behaviour for change (Seo, Taylor, Hill, Zhang, Tesluk, & Lorinkova, 2012); implementation of innovation (Michaelis, Stegmaier, & Sonntag, 2010); voicing concerns about change (Cinite & Duxbury, 2018); job satisfaction (Yang, 2016) and reduce resistant behaviour towards change (Seo et al, 2012); and turnover intention (Cunningham, 2006;Shin, Seo, Shapiro, & Taylor, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Individuals with commitment to change would feel attached and strive to make the change a success (Herscovitch & Meyer, 2002). Previous research proved that com-mitment to change could increase behavioural support for change and creative behaviour for change (Seo, Taylor, Hill, Zhang, Tesluk, & Lorinkova, 2012); implementation of innovation (Michaelis, Stegmaier, & Sonntag, 2010); voicing concerns about change (Cinite & Duxbury, 2018); job satisfaction (Yang, 2016) and reduce resistant behaviour towards change (Seo et al, 2012); and turnover intention (Cunningham, 2006;Shin, Seo, Shapiro, & Taylor, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Servant leadership is a widely accepted leadership style (Blanchard, 2018). While an instinctively exciting idea, it is methodically indistinct and not yet supported by present research (Cinite & Duxbury, 2018). Servant leadership is a hypothetical structure that executed to develop influential organizations.…”
Section: Barriers To Organizational Changementioning
confidence: 70%
“…Further, Cinite and Duxbury (2018) demonstrated that staff most often resist change by voicing their concerns about change. Second, the staff who are focused on the change are most likely to voice their concerns to their superiors within the chain of command.…”
Section: Barriers To Organizational Changementioning
confidence: 99%
“…El sentimiento de compromiso abarca una dimensión normativa (estrategias para realizar el cambio), afectiva (deseo de formar parte del cambio) y efecto continuo (anticiparse a las posibles consecuencias de no adaptarse al cambio). En este sentido, se debe aclarar que aunque el compromiso por el cambio es relativo a una fuerza, esta no debe ser obligatoria, el compromiso debe fluir y debe ser opción propia de la persona, aunque esta se vea influenciada por factores externos (Cinite & Duxbury, 2018).…”
Section: Estrategias De Cambio Organizacionalunclassified